Global warming - Blashfield, Jean F.; Black, Wallace B. (Chicago : Childrens Press, 1991)
Describes the gradual warming of the planet, its causes and effects, and ways in which it can be combatted.
Includes index.
School Library Journal.
6.5
5-8
Keywords: Global warming -- Juvenile literature; Global warming; Global warming